Penanaman Nasionalisme Siswa Melalui Ekstrakurikuler Seni Tari di SD Negeri Cikokol 1 Kota Tangerang - Nabilla Oktaviani Rizki; Eka Yulyawan Kurniawan; Ino Budiatman (Pusat Riset dan Inovasi Nasional, 2025)
The cultivation of nationalism in students through extracurricular traditional dance activities at SD Negeri Cikokol 1, Tangerang City focuses on fostering a sense of patriotism and respect for Indonesian culture. This study aims to explore the role of traditional dance in instilling nationalism values in students. Using a qualitative approach with a descriptive method, data were collected through interviews, observations, questionnaires, and documentation. The findings indicate that extracurricular traditional dance significantly contributes to cultivating nationalism, with students showing increased pride in Indonesian culture, enhanced cooperation, and affection for cultural diversity. However, there remains room for further development, particularly in the aspects of respect for teachers and fostering deeper love for Indonesian culture. The study suggests that teachers emphasize the integration of cultural values in extracurricular activities and provide more intensive guidance. The implications of this research highlight the importance of traditional dance as a medium for fostering nationalism character development, which can be applied in educational curricula.